THE DEVELOPMENT OF STRATEGY OF INDONESIAN NAVAL REPAIRMENT AND MAINTENANCE FACILITY (FASHARKAN) TO SUPPORT THE READINESS OF BATTLESHIPS IN FIRST FLEET COMMAND BY USING TOWS METHOD (CASE STUDY FASHARKAN JAKARTA) - Kuncoro Kuncoro; Okol Sri Suharyo; Avando Bastari (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT Indonesian Naval Repairment and Maintenance Facility that has location in Jakarta is an organization which has duties and tasks to repair and maintain the KRI. To implement their complexity tasks and fulfill the developing of Naval technology, it needs equipment that requires with high technology and professional personel suitable with their fields. The purpose of this research is to determine the alternative development strategy of Indonesian Naval Repairment and Maintenance Facility Jakarta. This study uses the TOWS analysis method (Treaths Opportunities weaknesses Strengths). TOWS analysis is used to formulate and provide alternatives in the development strategy of Fasharkan Jakarta. Based on the results of the TOWS matrix analysis, the SO Strategy consists of 6 (six) strategic steps, the ST Strategy consists of 6 (six) strategic steps, the WO Strategy consists of 9 (nine) strategy steps and WT strategy consists of 4 (four) steps strategy. Based on weighting are using the EFAS and IFAS matrices, the chosen strategy is the WO Strategy, so that the WO strategy becomes the first alternative. Based on the results of the classification of elements in the WO strategy, there are 5 (five) levels of hierarchical structure. In this hierarchical structure, it can be seen that the sub-strategy (WO5) is at level V. Then the sub-strategies (WO1) and (WO4) are at level IV. At level III, it consists of 4 (four) sub strategy, they are (WO2); (WO6); (WO7); (WO8). At level II, it is named the sub strategy (WO3). At level I sub strategy is (WO9). Keywords: Fasharkan Jakarta, Development Strategy, TOWS.